An analysis of digital literacy skills of high school students in biology - Sukma, Ridho Ilafi; Purwianingsih, Widi; Amprasto, Amprasto (Universitas Islam Negeri Sumatera Utara, 2023)
Digital literacy is a crucial skill for understanding information from various sources, such as the use of the internet and other digital media as a learning resource. Navigating the internet is an important skill to master to keep updated with the development of information and communication technology in the era of Industrial Revolution 4.0 and to master one of the 21st-century skills. Skills that someone should have in digital literacy include internet searching, hypertextual navigation, evaluating information, and synthesizing information. This study aims to determine the digital literacy skills of tenth-grade high school students in biology class. The research method follows the quantitative descriptive method. The population and sample were 62 tenth-grade high school students. The data collection technique is in the form of questionnaires focusing on four aspects of digital literacy. The results indicate that the digital literacy of tenth-grade high school students with an average score of 44% is in the fair category. Meanwhile, the results for each aspect of the digital literacy indicator obtained different scores, namely internet searching at 47% (fair), hypertext navigation at 27% (fair), evaluating information at 40.32% (fair), and synthesizing information at 60.48% (good). This research suggests how stakeholders can issue policies as a basis for improving students' digital literacy to support the learning process focusing more on 21st-century skills.